Instagram Advertising Influencers and Customer Engagement among Undergraduate University Students in Port Harcourt - Wike, Isaiah N. Binaebi Gloria Bello, Ovuah, Beatrice Wugate, Dumle E Potts-Johnson, Ethel Ebitimi (Journal for Studies in Management and Planning, 2025)
This study investigated the role of Instagram advertising influencers in shaping electronic word-of-mouth (eWOM) among undergraduate students in Port Harcourt, Nigeria. The study adopted perceived interactivity and hedonic content as dimensions of Instagram advertising influencers. Using a purposive and convenience sampling approach, data were collected through an online survey administered via SurveyMonkey to 400 students across three major universities in Port Harcourt, with 380 valid responses returned. Measurement scales were adapted from established literature, and reliability analysis confirmed adequate internal consistency. The findings reveal that Instagram influencers significantly influence consumer engagement and eWOM. Perceived interactivity was shownto enhance conversational exchanges, and improve brand advocacy, while hedonic content amplified experiential value, enjoyment, and emotional resonance, which in turn stimulated positive eWOM. The study concludes that Instagram influencers play a key role in shaping electronic word of mouth among university students in Port Harcourt, Rivers State, Nigeria through perceived interactivity and hedonic content. The study recommends the need for Instagram influencers to design interactive, easy-to-use brand communication techniques, encourage user-generated content, and balance hedonic elements with informative value to sustain trust and long-term engagement.
Keywords: : Consumer Engagement; Electronic Word-of-Mouth (eWOM); Hedonic Content; Instagram Influencers; and Perceived Interactivity